8 - Place, Public Good and Higher Education in South Africa - Molebatsi, Palesa (Journal of Higher Education in Africa, 2022)
Worsening poverty and inequality continue to affect large segments of the South African population. Universities are critical in contributing to overcoming these challenges. This article looks at the relationship between South African universities and the communities and places in which they are located. The history of South African higher education shows different kinds of relationships with the places in which universities were set. Data collected from interviews in 2018 with key informants in South African universities notes their criticisms of government development policies that lacked vision with regard to the development of place-based relationships for the public good. This data indicates that in the absence of an enabling policy framework to link communities and places, certain universities, individuals who work in them and members of communities around universities have developed their own approaches. I argue that these activities indicate actions by certain members of a spatial community, which can be understood as practices associated with a public sphere. Through this process individuals and institutions can play a central role in defining and contextualising the public good role of universities in their communities.